Limit Pricing and the (In)Effectiveness of the Carbon Tax - Saraly Andrade de Sá; Julien Daubanes (Center for Economic Studies and ifo Institute (CESifo), 2014)
Demand for oil is very price inelastic. Facing such demand, an extractive cartel induces the highest price that does not destroy its demand, unlike the conventional Hotelling analysis: the cartel tolerates ordinary substitutes to its oil but deters high-potential ones. Limit-pricing equilibria of non-renewable-resource markets sharply differ from usual Hotelling outcomes. Resource taxes have no effect on current extraction; extraction may only be reduced by supporting its ordinary substitutes. The carbon tax applies to oil and also penalizes its ordinary (carbon) substitutes, inducing the cartel to increase current oil production. The carbon tax further affects ultimately-abandoned oil reserves ambiguously.
Keywords: Q30; L12; H21; Q42; 330; carbon tax; limit pricing; non-renewable resource; monopoly; demand inelasticity; substitutes subsidies